Monoclonal antibody to a plasma membrane antigen of neurons. - Eisenbarth, G S (1979)
Fusion of spleen cells from a mouse immunized with chicken embryo retina cells with clonal mouse myeloma cells yielded a lymphocyte hybrid cell line that produced antibody that bound to neural tissue such as retina, brain, spinal cord, and dorsal root ganglia but not to other tissues tested. The antigen was shown by indirect immunofluorescence to be associated with plasma membranes of most, or all, neuron cell bodies in chicken retina, but little or no antigen was detected on axons or dendrites, Müller cells, or retina pigment cells. The activity of antigen A2B5 is relatively stable at 100 degrees C, is insensitive to trypsin, exhibits the solubility properties of a ganglioside, and is destroyed by neuraminidase. Antibody A2B5 cytotoxicity against retina cells is inhibited by a GQ ganglioside fraction from bovine brain (estimated half-maximal inhibition at 0.2 microM) or by N-acetylneuraminic acid (half-maximal inhibition at 5000 microM) but not by other purified gangliosides tested. These results suggest that the antigen is a complex ganglioside in plasma membranes of retina neuron cell bodies but not axons or dendrites.